KUALITAS PELAYANAN PEMBUATAN KARTU TANDA PENDUDUK ELEKTRONIK DI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Amini Aprindawati; Isabella Isabella; Doris Febriyanti (Jurnal Pemerintahan dan Politik, 2019)
The title of this thesis are appointed based on the identification of existing problems, related to the service of the creation of the E-ID CARD that is still experiencing constraints in the manufacturing process, so that the ministries still do not meet the standards of service that is oriented to the satisfaction of the users of the service. This research uses the theory that there is a mention of Zeithaml five dimensions of service quality: Tangibels (tangibles), Resposiveness (responsiveness), Reliability (reliability), Assurance (assurance) and Emphaty (empathy). The method of this research is descriptive research using qualitative approach. The results of this study showed that the quality of public services in district Talang Kelapa already apply dimensions Tangibel, Realiability, Responsiviness, Assurance and Emphaty and their charge indicators will. But there are several indicators that have not run in accordance with the wishes of the community, for example: Discomfort place service including facilities and infrastructure are not yet complete, yet his employees in using the tools, services and ketidakramahan employees in the service of process.Keywords : Services, Public Services, The Quality Of Public Services.